Apoptotic cell identification: An in-vivo study during induction treatment of childhood acute lymphoblastic leukemia - Pudjo H Widjajanto; AJP Veerman; Sutaryo Sutaryo (Indonesian Pediatric Society, 2006)
Background Acute lymphoblastic leukemia (ALL) in children hashigh cure rate but it can cause death due to the side effects oftreatment or to the disease itself. Thus the evaluation on responseof treatment is important and may predict the prognosis. Sinceapoptosis can be induced by chemotherapy, it is thought that thenumber of leukemic cells that undergo apoptosis may reflect drugsensitivity and cytoreduction rate, thus it may correlate with prog-nosis.Objective To detect apoptotic cells in peripheral blood of childrenwith ALL during the first week of treatment.Methods We conducted a cross sectional study on 58 childrenwith newly diagnosed ALL treated in Department of Child Health,Sardjito Hospital, Yogyakarta. Apoptotic cells were detected onsmears of buffy coat made from peripheral blod and stained withMay-Grunwald Giemsa. The apoptotic cells viewed under light mi-croscope within 12 time points during 7 days after treatment started.Results Apoptotic cells were identified in 3 of 58 patients withindex range of 4.2% to 36.2%.Conclusion Apoptotic cells can be detected in peripheral bloodwith simple method. The explanation of why not all blood smearsviewed showed these cells need further study. It may due to themethods or the apoptotic process itself.